Zeolite Beta Formation from Clear Sols: Silicate Speciation, Particle Formation and Crystallization Monitored by Complementary Analysis Methods. Issue 43 (7th September 2016) - Castro, Maria; Haouas, Mohamed; Lim, Ivy; Bongard, Hans J.; Schüth, Ferdi; Taulelle, Francis; Karlsson, Gunnel; Alfredsson, Viveka; Breyneart, Eric; Kirschhock, Christine E. A.; Schmidt, Wolfgang
Abstract: The formation of silicate nanoaggregates (NAs) at the very early stages of precursor sols and zeolite beta crystallization from silicate nanoparticles (NPs) are investigated in detail using a combination of different analysis methods, including liquid‐state 29 Si, 27 Al, 14 N, and 1 H NMR spectroscopy, mass spectrometry (MS), small‐angle X‐ray scattering (SAXS), X‐ray diffraction (XRD), and transmission electron microscopy at cryogenic temperatures (cryo‐TEM). Prior to hydrothermal treatment, silicate NAs are observed if the Si/OH ratio in the reaction mixture is greater than 1. Condensation of oligomers within the NAs then generates NPs. Aluminum doped into the synthesis mixtures is located exclusively in the NPs, and is found exclusively in a state that is fourfold connected to silicate, favoring their condensation and aggregation. These results are in agreement with general trends observed for other systems. Silicate NAs are essential intermediates for zeolite formation and are generated by the aggregation of hydrated oligomers, aluminate, and templating cations. Subsequent further intra‐nanoaggregate silicate condensation results in the formation of NPs. 1 H and 14 N liquid NMR as well as diffusion ordered spectroscopy (DOSY) experiments provide evidence for weakly restricted rotational and translational mobility of the organic template within NAs as a consequence of specific silicate–template interactions. NAs thus appear as key species in clear sols, and their presence in the precursor sol favors silicate condensation and further crystallization, promoted either by increasing the Si/OH ratio or by heating. Abstract : Mechanism analysis : The formation of zeolite beta (see figure) is monitored by liquid‐state NMR, ESI‐MS, SAXS, XRD, cryo‐TEM, and HRSEM. The complementary methods allow the monitoring of all processes occurring during silicate speciation and particle formation up to the final stages of zeolite beta crystallization. The analyses reveal the zeolite formation mechanism and allow the identification of crucial species as well as spectators.